The implementation of modern genetic improvement methods in wildlife - Neser, Frederick, author; Fair, Mike, author; van Wyk, Japie, author; Lubout, Paul, author; Josling, Charné, author; de Waal, HO, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
In recent times the economic value of wildlife has extended beyond merely hunting and eco-tourism. The demand for exotic and alternative meat sources worldwide has resulted in a shift on emphasis placed on the improvement of production and reproduction traits in the wildlife sector. This trend is in line with the current genetic improvement of commercial farm animals. However, the over emphasis placed on single trait selection, like horn length and colour, without considering the genetic correlations that exist between all possible traits, could have detrimental effect on the important traits of fertility and adaptation. Unfortunately these traits are normally difficult to measure, lowly heritable and negatively correlated with production. To overcome these obstacles it is necessary to have proper phenotypic and genomic data to implement modern genetic evaluation methodologies. To avoid mistakes made in the traditional livestock industry, the defining of sustainable and balanced selection goals is of paramount importance. Apart from the benefits of genetic improvement, conservation and diversity can also be maintained and improved, while inbreeding can be monitored and controlled.
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.